Morphology and phylogeny reveal Leucocoprinus atroferrugineus (Agaricaceae), a new species from Pakistan - Ishaq, Muhammad; Khan, Muhammad Binyamin; Lu, Wenhua; Asif, Muhammad; Tarafder, Entaj; Sana; Fiaz, Muhammad; Karunarathna, Samantha C.; Khalid, Abdul Nasir; Wen, Ting Chi (Phytotaxa, 2025)
Leucocoprinus atroferrugineus sp. nov. is described from Buner District, Pakistan, based on morphological features and molecular evidence. This species is characterized by the presence of dark, reddish-brown, areolate-fibrillose squamules on the pileus, which become dull reddish brown to reddish brown towards the margin; a hollow stipe with a pale pinkish apex; dark fibrils below the annulus, turn orange and eventually dark when scratched; and the presence of an annulus. The basidiospores are large, ellipsoid to amygdaliform. Detailed morphological characteristics and phylogenetic analysis using the ITS rDNA barcode region confirm the new species. A description with comprehensive discussion, illustrations, and phylogenetic analysis results of the new species are provided.